Loss of Aquaporin-3 in Placenta and Fetal Membranes Induces Growth Restriction in Mice - Seo, Min Joon (Dev Reprod, 2018)
Aquaporin (AQP) 3, a facilitated transporter of water and glycerol, expresses in placenta and fetal membranes, but the detailed localization and function of AQP3 in placenta remain unclear. To elucidate a role of AQP3 in placenta, we defined the expression and cellular localization of AQP3 in placenta and fetal membranes, and investigated the structural and functional differences between wild-type and AQP3 null mice. Gestational sacs were removed during mid-gestational period and amniotic fluid was aspirated for measurements of volume and composition. Fetuses with attached placenta and fetal membranes were weighed and processed for histological assessment. AQP3 strongly expressed in basolateral membrane of visceral yolk sac cells of fetal membrane, the syncytiotrophoblasts of the labyrinthine placenta and fetal nucleated red blood cell membrane. Mice lacking AQP3 did not exhibit a significant defect in differentiation of trophoblast stem cells and normal placentation. However, AQP3 null fetuses were smaller than their control litter mates in spite of a decrease in litter size. The total amniotic fluid volume per gestational sac was reduced, but the amniotic fluid-to-fetal weight ratio was increased in AQP3 null mice compared with wild-type mice. Glycerol, free fatty acid and triglyceride levels in amniotic fluid of AQP3 null mice were significantly reduced, whereas lactate level increased when compared to those of wild-type mice. These results suggest a role for AQP3 in supplying nutrients from yolk sac and maternal blood to developing fetus by facilitating transport of glycerol in addition to water, and its implication for the fetal growth in utero.